Lectus eburneus Les lits funéraires en ivoire à Cumes et dans le monde romain - Cormier, Anselme (Collection du Centre Jean Bérard, 2022)
The funerary beds of the Roman period come from an ancient tradition, whose origins, beyond the Greeks, can be traced to the earliest historical periods, in Egypt and in the Near East. Since the 19th century, excavations have produced many vestiges, most of them dating back to between the 2nd century BC up to the 2nd century AD; they echo pieces found in domestic contexts which, though less numerous, allow interesting comparisons and a better understanding of the topic. The large variety of the identified models led to develop a detailed typology of these forms, from the most ancient ones up to those of the Roman period. The publications significantly changed our knowledge of the beds adorned with bronze as well as those adorned with bone carvings. By contrast, instances of ivory beds are extremely rare, whether it be in Italy or in the whole Roman world. Thus, the discovery at Cumae of the vestiges of three ivory beds, adorned with this precious material, serves as essential and unique testimony. The fragments were mixed with the bones of the deceased and placed in urns, themselves located in important mausoleums. Their remarkable quality and meticulous workmanship, clearly visible upon some pieces, which survived the destruction caused by the cremation, as well as the iconographic staged patterns, testify to the conspicuous intentions of their owners, anxious to show their social status, their wealth and their virtues to the living. The contextualization and close study of these three beds, along with a comparison with the known examples, led for each of them to an attempt at a graphic restoration, as a prerequisite for an iconographical and iconological analysis. The achieved results, correlated with the mausoleums where they were found, led to a much more precise understanding of those beds and of the prominent position they enjoyed at the funeral ceremony.